Self-concept and Locus of Control as Internet Addiction Predictors among Undergraduate Students - Abdulkareem, Habibat Bolanle; Bello, Jamiu Babatunde; Salami, Tunde Adeniyi (Bumi Publikasi Nusantara, 2023)
This study investigated the predictive power of students’ locus of control as well as a self-concept on ability levels of internet addiction among undergraduate students of al-hikmah University- Ilorin. A correlation survey research design was adopted for the study. Five research questions were answered and five null hypotheses were tested. The study was conducted in the Ilorin Metropolis of Kwara State. A convenient sampling technique was used to select 550 participants that use the e-library and Information and Communication Technology (ICT) regularly. Instruments such as the Self-Concept Scale, Locus of Control Scale and Internet Addiction Scale were adopted to gather information from the respondents. Data collected were analyzed using Pearson product-moment correlation (PPMC) and regression analysis to answer both the research questions and the null hypotheses were tested at 0.05 level of significance. Findings revealed that self-concept, internal and external locus of control and gender significantly predicts internet addiction among undergraduate students of Al-Hikmah. The combination of self-concept and locus of control significantly predicts students’ internet addiction among undergraduate students of Al-Hikmah. We recommended that School counsellors should build self-reliance in external control-oriented students to strive harder even when anticipating that luck and fate could determine their Success. School counsellors should support internal control-oriented students on the need to develop self-efficacy and competency and use opportunities to facilitate them to attain their desired goals. The school management should enlighten their students on how to use their efforts in the use of the internet and advocate how to avoid being addicted to it.